The Design of Flexible Pervasive Electronic Health Record (PEHR) - Abd Ghani, M. K.; Lee, C. W. (2011)
Pervasive Electronic Health Record provides private medical history record for an individual within a healthcare system. By using pervasive storage devices, patient’s EHR can be accessed electronically by authorize healthcare providers and healthcare professionals in the right place at the right time. The storage device includes item such as PDA, mobile phone, smart card, laptop and USB flash memory which are at the possession of patients, and are therefore readily available at all times. This paper designs a flexible pervasive electronic health record system for the seamless access of the previous patient EHR. The system was developed after an analysis of clinical consultation workflow and systematic review of other health information system.